The peculiarities of structural modificaions of CVD polycrystalline diamond coatings by heavy doping with boron; Energy Fluxes and Radiation Effects (EFRE-2016) - Okhotnikov V. V. Vitaly Vladimirovich (2016, 2016)
Title screen